Inventing the self, fictionalizing the other: false memories in the theatre of mario vargas llosa - Melendez, Priscilla (Symposium: A Quarterly Journal in Modern Literatures, 2012)
The Peruvian writer Mario Vargas Llosa, one of the most prolific and distinguished Spanish American novelists of the twentieth century and the winner of the 2010 Nobel Prize in Literature, is also the author of eight plays, which have frequently been overshadowed by his narrative production. Going beyond the relationship traced by critics between his novels and his plays, this essay underscores the prevalence in his theatrical work of a tug of war between biographical and autobiographical voices as part of a fundamental exploration of real and fictional memory. From Vargas Llosa's early plays of the 1980s to his most recent ones, he has frequently dramatized the life of both real and imaginary, famous and infamous others and selves, creating the illusion that the audience is witnessing someone's life trajectory. This is the analytical angle from which this essay approaches not only Vargas Llosa's first play, La seorita de Tacna (1981), but in particular one of his most recent ones, Odiseo y Penélope (2007). In both analyses, the definitions of biographical and autobiographical discourses are interpreted in light of theatrical representation, underscoring in this way the subjective, dramatic, and metaphorical perspectives of these expressions. © 2012 Taylor and Francis Group, LLC.
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/013-132-663-189-569
Keywords: La seorita de Tacna; Odiseo y Penélope; Vargas Llosa; autobiography; dept.wll; theatre

Assessing strategic cultural competency: holistic approaches to student learning through media - Hammer, Judith; Swaffar, Janet (The Modern Language Journal, 2012)
The current study investigated the impact of a German television program on changes in 4th-semester German students' reflections on cultural perceptions over the course of 1 semester. Sixty-nine students at the University of Texas at Austin watched 4 episodes of the popular German television program Lindenstrasse. After viewing, students were asked to reflect in written response papers on cultural features and patterns of behavior and on cultural differences and similarities. The study results suggest that students' perceptions of another culture can become more sophisticated when being exposed to authentic filmic material and asked to reflect in writing about observed plot features and cultural manifestations. The key to these results is a strategy for assessing not just students' recall of cultural content, but also their strategic competencies in negotiating cultural difference. Changes in students' cognitive styles were tracked by a scale that rewards students' strategic ability tomanage details of cultural knowledge and sociolinguistic content, including the following categories: (a) rhetorical organization; (b) content; (c) comparative point of view; and (d) interpretive substance. The article provides a model for the assessment of cultural competency (MACC), which can be adapted to assess students' engagement with the culture represented in various materials.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/036-725-840-773-327 tex.eissn: [object Object] tex.unique-id: [object Object]
Keywords: dept.wll

Afro-Latino/a identities: challenges, history, and perspectives - Latorre, Sobeira (Anthurium: A Caribbean Studies Journal, 2012)
1 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/009-566-266-159-36X tex.type: [object Object]
Keywords: dept.wll

Utopian worlds: vico, la capria and mazzotta - Palma, Giuseppina (MLN - Modern Language Notes, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/014-683-427-020-179 tex.type: [object Object]
Keywords: dept.wll

La luz Y la guerra: el cine de la revolucion mexicana edited by fernando fabio sánchez and gerardo garcía muñoz - Rodriguez, R Hernandez (The Latin Americanist, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/012-503-311-969-872 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed

Mañana forever? Mexico and the mexicans by jorge g. castañeda - Rodriguez, R Hernandez (The Latin Americanist, 2012)
0 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/001-812-351-150-474 tex.type: [object Object]
Keywords: dept.wll; peer-reviewed